2021
DOI: 10.5194/nhess-2021-66
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using high-resolution regional climate models to estimate return levels of daily extreme precipitation over Bavaria

Abstract: Abstract. Extreme daily rainfall is an important trigger for floods in Bavaria. The dimensioning of water management structures as well as building codes are based on observational rainfall return levels. In this study, three high-resolution regional climate models (RCMs) are employed to produce 10-year daily rainfall return levels and their performance is evaluated by comparison to observational return levels. The study area is governed by different types of precipitation (stratiform, orographic, convectional… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…The projected future changes in extreme discharges may be attributed in part, to the climatological reference dataset, as it affects the performance of the hydrological model as well as the CCS through bias adjustment (Gampe et al, 2019;Meyer et al, 2019;Willkofer et al, 2018). Precipitation in high altitudes (e.g., the Alps) may be undercaptured (Westra et al, 2014;Poschlod, 2021;Prein and Gobiet, 2017;Rauthe et al, 2013;Poschlod et al, 2020;Willkofer et al, 2020) resulting in an underestimation of observed precipitation in these regions, especially of extreme values. Assuming a temporally stationary bias, changes in the extremes might be overestimated due to an over-adjustment of the distribution of the reference period towards underestimated observations compared to the future periods.…”
Section: Discussionmentioning
confidence: 99%
“…The projected future changes in extreme discharges may be attributed in part, to the climatological reference dataset, as it affects the performance of the hydrological model as well as the CCS through bias adjustment (Gampe et al, 2019;Meyer et al, 2019;Willkofer et al, 2018). Precipitation in high altitudes (e.g., the Alps) may be undercaptured (Westra et al, 2014;Poschlod, 2021;Prein and Gobiet, 2017;Rauthe et al, 2013;Poschlod et al, 2020;Willkofer et al, 2020) resulting in an underestimation of observed precipitation in these regions, especially of extreme values. Assuming a temporally stationary bias, changes in the extremes might be overestimated due to an over-adjustment of the distribution of the reference period towards underestimated observations compared to the future periods.…”
Section: Discussionmentioning
confidence: 99%